(untitled) (Indian Journal of Animal Production and Management, 2013)
90 days trial conducted in Kushal village, Palanpur takula of banaskantha district of North Gujarat. Fourteen lactating Kankrej cows were divided in to dietary treatments T1 (control) and T2 (probiotics). The results revealed that supplementing probiotics to latating Kankrej cows signficantly improved fat percent, 4% FCM while milk production and return as percent of feed cost were increased but remained statistically similar as compared to control.